Modern diagnosis of pulmonary tuberculosis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
In view of the need to maintain a high index of suspicion for tuberculosis (TB) in elderly patients and in patients with HIV infection, I would like to add to the reservations expressed about the guidelines for the management of adults lower respiratory tract infections.In modern conditions, when highly informative research methods have become available, the difficulties of diagnosing TL have not decreased at all. Now it is impossible to focus on the ideas of the recent past, which attribute only the discrepancy between clinical and pathomorphological diagnoses to errors in the diagnosis of tuberculosis. A serious omission is the late detection of TL, when the process has already acquired an irreversible form, and the patient has managed to infect many of the people around him. The role of such an exogenous infection in the development of tuberculosis in adults has been emphasized by recent studies, which have forced a revision of established ideas about the pathogenesis of tuberculosis.